Bloody pericardial tamponade in a child treated for pneumonia mimiking a lung tumor and infiltration of the heart - Haponiuk, Ireneusz; Chojnicki, Maciej; Jaworski, Radoslaw; Zielinski, Jacek; Irga-Jaworska, Ninela; Gierat-Haponiuk, Katarzyna; Sroka, Mariusz (Contemporary Oncology/Współczesna Onkologia, 2013)
We present the dramatic course of a female 5-year-old child with pneumonia and symptoms similar to local compression of the pericardium by a tumorous mass originating from the left lung. The child was treated with antibiotics for pneumonia with bilateral pleural effusions that required chest drainage. On the 10th day of therapy there was sudden anemia observed with the echocardiographic finding of acute cardiac tamponade. The child was referred for emergency life-saving surgical intervention. The chest was opened via a minimally invasive mini-incision in the area of the xiphoid process and bloody tension pericardial effusion was evacuated. The laboratory and histopathology investigations were not specific for neoplastic disease or tuberculosis infection. In the further observation the girl recovered and was discharged home two weeks after tamponade drainage. Fortunately our initial suspicion of neoplastic disease was not proved; nevertheless we would like to emphasize the need for oncologic vigilance in similar cases.